What Is Expected from a Facial Trauma Caused by Violence? - Douglas Rangel Goulart; Lucas do Amaral Colombo; Márcio de Moraes; Luciana Asprino (eJournal of Oral Maxillofacial Research, 2014)
Objectives: The aim of this retrospective study was to compare the peculiarities of maxillofacial injuries caused by interpersonal violence with other etiologic factors.